(untitled) (Journal of Global Accounting, 2023)
This study examined the effect of the fraud pentagon model in fraud assessment in Deposit Money Banks in Nigeria from 2005-2014. The study adopted the ex-post facto research design. The population of the study was centred on the performance indices of the fifteen (15) banks that are currently listed on the Nigerian Stock Exchange from 2005 to 2014. Data were obtained from the published financial statements of the fifteen (15) banks for a ten (10) year period spanning from 2005-2014. The multiple regression technique was the main statistical tool used in the study. In order to verify the quality of the data used, Variance Inflation Factor (VIF) was employed to test for multicollinearity among the variables. The result showed that the Behavioural Trait (BET) factor has a positive significant effect on fraud risk. The study concluded that fraud pentagon model offers an effective means in assessing fraud risk in the financial statement by incorporating the fifth element–‘the behavioural trait’ as one of the fraud risk factors. This would effectively enhance auditors’ detection of material misstatement in the financial statement of DMBs in Nigeria.